Evaluating miscarriage incidence after COVID-19 vaccination - Fariba Shahraki-Sanavi; Sajad Sahab-Negah; Sairan Nili; Parvin Mangolian shahrbabaki; Alireza Ansari-moghaddam; Mohammad Fereidouni; Abtin Heidarzadeh; Mostafa Enayatrad; Sepideh Mahdavi; Roqayeh Aliyari; Mansooreh Fateh; Hamidreza Khajeha; et al. (Scientific Reports)
Abstract COVID-19 infection during pregnancy might be associated with maternal complications. This study aimed to investigate the impact of COVID-19 vaccination on the risk of miscarriage. This cohort study included 26,701 women of reproductive age (15–49) who were vaccinated with different vaccines (Sinopharm, Sputnik V, AZD1222 and CoVIran Barekat) between April 2021 and August 2022 in seven cities in Iran. Among them 459 women were pregnant and included in this analysis. All pregnant women were followed up until the end of their pregnancy. The mean age (standard deviation) of pregnant women was 31.7 (6.8) years. Among them, 50 miscarriage cases occurred. The cumulative incidence of miscarriage was 10.9%; 95% confidence intervals [CI] 8.0–13.8) in total, and 11.0% (5.9–16.1), 9.7% (4.4–14.9), 12.0% (5.9–18.2), and 11.1% (4.2–18.0) for AZD1222, Sputnik V, Sinopharm and Barekat vaccines respectively. Cumulative incidence rates by vaccine brands were not statistically significant (P value = 0.962). The mean (SD) time interval between conception and vaccination was 3.5 (3.8) weeks and it was 7.5 (2.7) weeks for the age of the fetus at miscarriage. In general, the miscarriage rate in women of reproductive age was 4.8 (95% CI 4.1–5.7) per 1000 women. The estimated incidence rates were not higher than expected; therefore, it can be argued that COVID − 19 vaccination with Sputnik V, Sinopharm, Barekat and AZD1222 does not increase the probability of miscarriage and the vaccines are therefore safe in this respect.